THE LEGALITY OF DENMARK’S ARTIFICIAL ISLAND (LYNETTEHOLM) IN INTERNATIONAL LAW OF THE SEA - Benita Viola; Muhammad Shalahuddin Yusuf (International Law Department, Faculty of Law Universitas Padjadjaran, 2021)
The Danish parliament approved the construction of an artificial island called Lynetteholm, which aims to house 35,000 residents and protect the Port of Copenhagen from rising sea levels. Construction of Lynetteholm will take approximately 50 years, and the island will be 2.6 km2 in size. Since the regulation regarding Artificial Island can only be found in the United Nations Convention on Law of the Sea 1982 (UNCLOS 1982) which is not complete regulatory support along with no other regulations that can provide specifications regarding the implementation rules for the construction of an artificial island, both provisions and prohibitions in the process of making Artificial Island. This long-term development could cause a damage towards the marine life and cause air pollution in the construction area due to heavy trucks, change in the ocean currents in the Danish and Swedish oceans due to the size of the island, and cause potential changes to the territorial sea boundaries of Denmark’s EEZ. As long as the legal regulations regarding Artificial Island have not been made specifically and in detail, large-scale and long-term construction of artificial islands that cause legal problems will continue to occur in the future. Therefore, the making of special rules regarding Artificial Island has become a real urgency at this time. Denmark has an obligation to conduct a re-assess regarding problems that may arise as well as those that are contrary to UNCLOS.